1983
DOI: 10.1007/bf01641358
|View full text |Cite
|
Sign up to set email alerts
|

Activity of ciprofloxacin (BAYo 9867) against pseudomonas aeruginosa and ampicillin-resistant Enterobacteriaceae

Abstract: We studied the in vitro activity of ciprofloxacin against 570 strains of ampicillin-resistant Enterobacteriaceae and 286 Pseudomonas aeruginosa strains. 95.26% of the Enterobacteriaceae and 53.45% of the P. aeruginosa were inhibited by 0.1 mg/l of ciprofloxacin. 2 mg/l of ciprofloxacin inhibited all of the Enterobacteriaceae strains and 4 mg/l all of the P. aeruginosa. We compared the activity of ciprofloxacin with that of temocillin in the Enterobacteriaceae strains. In the P. aeruginosa strains, classified a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
10
0

Year Published

1984
1984
1988
1988

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…Significantly higher peak levels of ciprofloxacin in serum were observed after multiple dosing (3.51 versus 2.26 ,g/ml; P < 0.01). Increased elimination half-life occurred after multiple dosing; this seems Ciprofloxacin is an investigational quinolone with superior in vitro activity over other DNA gyrase inhibitors (5,17). Single-dose pharmacokinetic and blister fluid penetration studies have been reported after oral and intravenous administration of ciprofloxacin (3, 4, 21), but no studies are available on blister fluid penetration after multiple doses.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Significantly higher peak levels of ciprofloxacin in serum were observed after multiple dosing (3.51 versus 2.26 ,g/ml; P < 0.01). Increased elimination half-life occurred after multiple dosing; this seems Ciprofloxacin is an investigational quinolone with superior in vitro activity over other DNA gyrase inhibitors (5,17). Single-dose pharmacokinetic and blister fluid penetration studies have been reported after oral and intravenous administration of ciprofloxacin (3, 4, 21), but no studies are available on blister fluid penetration after multiple doses.…”
mentioning
confidence: 99%
“…Ciprofloxacin is an investigational quinolone with superior in vitro activity over other DNA gyrase inhibitors (5,17). Single-dose pharmacokinetic and blister fluid penetration studies have been reported after oral and intravenous administration of ciprofloxacin (3,4,21), but no studies are available on blister fluid penetration after multiple doses.…”
mentioning
confidence: 99%
“…Lower MICs of ciprofloxacin for members of the family Enterobac-teriaceae (including P-lactamase-producing strains) (1, 2, 4-6, 9) and slightly higher MICs of ciprofloxacin for Pseudomonas aeruginosa (including strains resistant to gentamicin or carbenicillin) (2,6,8) were found compared with those of available antimicrobial agents. Other gram-negative and certain gram-positive bacteria were also susceptible to ciprofloxacin.…”
mentioning
confidence: 89%
“…For instance, both the Providencia genus and enterococci species were fully identified in only one study each (7,12), and the susceptibility of all of the coagulase-negative staphylococcal species has not been previously reported (6,11). Moreover, the activity of ciprofloxacin against strains isolated from Southern Europe has been scarcely evaluated (18).…”
mentioning
confidence: 99%